Evaluation of Biocontrol Potential of Steinernema thermophilum Formulation (Biogel) against Some important Lepidopteran Crop Pests (Indian Journal of Nematology, 2024)
Insect pests cause serious damage to agricultural crops throughout the world. In order to control their infestation and increase crop production, farmers rely on synthetic pesticides that are available in the market. But these pesticides deteriorate the environment and also have negative impacton non-target organisms. So, for safer production, chemical control has been suggested to be replaced with some environmentally safe biological control method. One such important group of biocontrol agents is Entomopathogenic nematodes (EPNs). In the present study, laboratory assays were conducted to evaluate the biocontrol potential of Steinernema thermophilum formulation (Biogel) against three insect pests,viz., Galleria mellonella, Spodoptera litura and Corcyra cephalonica. Late instar larvae of all insect pests were exposed to four different concentrations of nematodes i.e. 20, 40, 60 and 80 IJ/L (infective juveniles/larva).All the insects tested were found to be susceptible to S. thermophilum formulation. Larval mortality increased with increase in concentration and exposure time. Out of the 3 insects, G. mellonella was found to be most susceptible to S. thermophilum.